(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2023)
Introduction: Vaccination is a very important part in the series of efforts to overcome the Covid-19 pandemic. The Covid-19 vaccination is an effort to protect the public, including teenagers, from transmitting the Covid-19 virus, which can cause illness. The purpose of this study was to describe the knowledge of junior high school students about the Covid-19 vaccine. Methods: This research is quantitative with a descriptive research design. This research was conducted at State Junior High School 6 Pekanbaru by considering the inclusion criteria, 89 samples were taken using random sampling method. The measuring instrument is a questionnaire that has been tested for validity and reliability. Results: Most of the respondents aged 14 years amounted to 44 respondents (49.4%). The number of female respondents was 66 respondents (74.1%) and 23 respondents (25.8%), class VII with 44 respondents (49.4%) and class VIII 45 respondents (50.6%), all respondents have had the Covid-19 vaccine and there is data that from class VII as many as 10 respondents (11.2%) and from class VIII as many as 8 respondents (8.9%) had been infected with Covid-19. The results showed that the level of knowledge of Junior High School Students about the Covid-19 Vaccine was 71 respondents (79.7%) with good knowledge, 16 respondents (17.9%) with sufficient knowledge and 2 respondents (2.2%) with less knowledge. Conclusion: The average junior high school student is well-informed about the Covid-19 Vaccine.